(untitled) (Bangladesh Medical Journal, 2014)
This experimental study was done in the Department of Physical Medicine and Rehabilitation, Bangabandhu Sheikh Mujib Medical University to find out the effects of lumbar corset on the patients with lumbar spondylosis. Ninety seven patients were selected in the study. Out of them 40(41.24%) were male and 57(58.76%) were female. The male to female ratio was 1:1.42. The mean age was 41.22 ± 8.52 years. The patients were divided into two groups, 50 patients in group A ( Treated with NSAID, activities of daily living instructions and lumbar corset) and another 47 patients in group B (Treated with NSAID and activities of daily living instructions only ). In both the groups, patients were treated for six weeks and assessed at 7 days interval. Improvement was noticed in both the groups in every visit but there was no difference in improvement between the groups till 4th week of treatment. At the end of treatment group A showed statistically significant difference in overall improvement in comparison to group B. So, from the present study, it may be concluded that lumbar corset is beneficial to the patients with lumbar spondylosis. DOI: http://dx.doi.org/10.3329/bmj.v42i2.18987 Bangladesh Med J. 2013 May; 42 (2): 55-59